Etnografia Multispecie e relazioni uomo-animale nel turismo someggiato - Zola, Lia (EtnoAntropologia, 2021)
Recent anthropological resoning, fostered by the ontological turn debate [Descola 2005, Viveiros de Castro 1998, Ingold 1988, 2001] tackled the issue of multispecies etnography: it deals with the lives and deaths of all the creatures that for decades have stayed on the margins of anthropology. After outlining the main features of domestication, my essay focuses on human-animal relations with an insight into a type of tourism with animals, which has not been specifically investigated so far: donkey trekking.